Clinical Pictures of Acute High-Altitude, Sickness - Marticorena, Emilio (1997)
A comprehensive review of Acute High-altitude Sickness is presented and discussed. Among them, Acute Pulmonary Edema and Acute Brain Edema are stressed for its clinical implicances. Preventive and therapeutic indication are puntualized.